State-Selected Reactivity of Carbon Dioxide Cations (CO2+) With Methane - Ascenzi, Daniela; Romanzin, Claire; Lopes, Allan; Tosi, Paolo; Žabka, Jan; Polášek, Miroslav; Shaffer, Christopher J.; Alcaraz, Christian (Frontiers in Chemistry, 2019)
The reactivity of CO2+ with CD4 has been experimentally investigated for its relevance in the chemistry of plasmas used for the conversion of CO2 in carbon-neutral fuels. Non-equilibrium plasmas are currently explored for their capability to activate very stable molecules (such as methane and carbon dioxide) and initiate a series of reactions involving highly reactive species (e.g. radicals and ions) eventually leading to the desired products. Energy, in the form of kinetic or internal excitation of reagents, influences chemical reactions. However, putting the same amount of energy in a different form may affect the reactivity differently. In this paper, we investigate the reaction of CO2+ with methane by changing either the kinetic energy of CO2+ or its vibrational excitation. The experiments were performed by a guided ion beam apparatus coupled to synchrotron radiation in the VUV energy range to produce vibrationally excited ions. We find that the reactivity depends on the reagent collision energy, but not so much on the vibrational excitation of CO2+. Concerning the product branching ratios (CD4+/CD3+/DOCO+) there is substantial disagreement among the values reported in the literature. We find that the dominant channel is the production of CD4+, followed by DOCO+ and CD3+, as a minor endothermic channel.